Poison information and education at your finger tips - Abd Razak, Dzulkifli (1996)
THE 1990S HAS SEEN THE ADVENT of the Internet, enabling the easy sharing of information across the globe. In Malaysia, its usage is booming at an estimated rate of 20% a month. This will invariably escalate further with the development of the planned Multimedia Super Corridor by 1998. At the same time, the profile of computer users are also changing with the increasing availability of personal computers at all levels of society. Computers too set the character of many workplaces, places of learning and even homes. Although the diffusion rate of the Internet among the general public is still low, the National Poison Centre (PRN) recognises that it is the way to create an informationrich Malaysia.